PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO PADA KOMPETENSI DASAR JURNAL PENYESUAIAN DI SMK NEGERI 1 GODEAN KELAS X - Hernadito Medika Putra; Sebastianus Widanarto Prijowuntato (Universitas Sanata Dharma, 2021)
This study aimed to develop a product of appropriate and qualified video-based learning media for Basic Accounting subjects in BC 3.10 and 4.10 on Journal of Adjustment for Grade X of vocational high school students specializing in the Institution Financial Accounting Expertise. The research method was Research and Development (RD). The steps utilized in this development were the development procedures according to Dick and Carey. This research was divided into 3 stages, namely: individual trial phase, small group trial, and large grup trials. The subject of the study were Grade X students of SMK Negeri 1 Godean specializing in the Institution Financial Accounting Expertise. The number of the subjects in this study were 43 students, consisting of 3 students for individual trials, 5 students for small group trials, and 35 students for large grup trials. Quality and feasibility assessment data along with suggestions for revision of video-based learning media products were collected using questionnaires. The analysis used was qualitative and quantitative in the form of an average. The results showed that video-based instructional media was decent used in learning in the classroom. This is indicated by the results of the assessment of video-based learning media on (1) validation of the material experts, included in the “good” criteria with an average score of 4.10, (2) validation of the phase I media experts, including the “good” criteria with an average score of 4.11, (3) validation of phase II media experts, included in the criteria of “very good” with an average score of 4.39, (4) validation of linguists, included in the criteria of “very good” with an average score of 4.53, (5) validation of stage I practitioners included in the criteria of “very good” with an average score of 4.76, (6) validation of practitioners of stage II included in the criteria of “very good” with scores an average of 4.70, (7) the results of the individual trial evaluation are included in the “very good” criteria with an average score of 4.21, and (8) the results of the small group trial evaluation are included in the “very good” criteria with an average score of 4, 46.Keywords: Development, video-based teaching media in basic, journal of adjustment